Personal and societal conflict of distributive principles and preferences - Ola Andersson; Marco Lambrecht; Topi Miettinen (Helsinki Graduate School of Economics, 2023)
Distributive justice principles are commonly used in societal debates to support policy positions and argue for their legitimacy. Prominent formal incarnations of such principles are the Rawlsian, Utilitarian, Efficient transfer (e.g. Pigou-Dalton), and Leaky-bucket transfer (e.g. Hammond) principles, but could also be formulated by the minimization of the Gini coefficient, for instance. We elicit preferences for these principles and collect distributive choices over income distributions in a large online experiment with participants from all walks of life. We randomly assign half of the sample to a resolution treatment when preferred principles are inconsistent with choices and study how personal conflicts are resolved. Except for the Gini principle, we find no statistically significant difference across initial subscriptions. However, among participants who are given the opportunity to resolve personal conflicts, the majority abandon their subscription to the principle. Efficient transfer principle is an exception, showing significantly more subscriptions than other principles after resolution. Additionally, we survey preferences over redistributive policies and find that the resolution mechanism reduces societal conflict. This finding has important implications for the elicitation of policy preferences in applied work.
Keywords: C91; D63; D71; D91; 330; social choice; Socratic method; policy preferences